Processos hidrológicos e balanço hídrico em lisímetros de drenagem em campo e mata nativa - Feltrin, Rafael Matias (2013)
The detailed representation of hydrological processes involved in soil water balance and the little knowledge about the influences of tropical forests has acquired great importance for the efficient management of water resources and a better understanding of the hydrological cycle. Therefore, is necessary to use of techniques that allow monitoring and the representation of involved variables, represent in a possible closer way the natural environment. This work aimed to investigate the dynamics of soil hydrological processes and the determination of the most adequate time scale for determining the water balance, utilizing drainage lysimeters containing undisturbed soil, installed in native grassland compared with the native forest, representative of the Atlantic Forest biome under the climatic conditions of the southern Brazil. The monitoring of the variables rainfall, runoff and drainage was performed through electronic rain gauges and the soil water content was monitored by electronic tensiometers installed at different depths of 10, 30 and 70 cm inside the lysimeters. The results showed that due to interception of solar radiation, the native forest provides the formation of an internal microclimate differentiated in relation to the external environment of native grassland, resulting in a lower input energy and exerting significant influences on the processes involved in the water balance. This difference in climatic conditions combined with soil characteristics, allows the lysimeter installed in native forest presents highest soil water storage capacity of water, being observed higher water contents in the soil, at all depths, compared the condition of native grassland. Consequently, the lysimeter installed in the native forest maintains the drainage flows for longer time than the lysimeter installed in the native field, being the drainage process influenced by the season and the antecedent soil moisture. Regarding the runoff, it is observed that the volumes per event are greater in native grassland than in native forest. The water balance calculation based on data monitored in the lysimeters shows that average daily actual evapotranspiration was 36.93% higher than in the native grassland lysimeter compared to lysimeter installed inside the native forest, having significant difference between the two environments. The lysimeters used in this study as well as the methodologies adopted for monitoring hydrological variables involved in water balance, did not show satisfactory results for the determination of evapotranspiration in daily periods since they are not able to represent the observed lags in speed that different processes occur in the interior of the soil profile. The timescale for events showed to be the most appropriate in determining the water balance in relation to the daily period and decendial period.